Marketing strategy and customer response of HERSTORY: designers wear by Aarong - Chowdhury, Fahmid Ahmed (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2017.